Artic-North Atlantic interactions and multidecadal variability of the thermohaline circulation - Jungclaus, J.; Haak, H.; Latif, Mojib; Mikolajewicz, U. (Journal of Climate, 2005)
Analyses of a 500-yr control integration with the non-flux-adjusted coupled atmosphere–sea ice–ocean model ECHAM5/Max-Planck-Institute Ocean Model (MPI-OM) show pronounced multidecadal fluctuations of the Atlantic overturning circulation and the associated meridional heat transport. The period of the oscillations is about 70–80 yr. The low-frequency variability of the meridional overturning circulation (MOC) contributes substantially to sea surface temperature and sea ice fluctuations in the North Atlantic. The strength of the overturning circulation is related to the convective activity in the deep-water formation regions, most notably the Labrador Sea, and the time-varying control on the freshwater export from the Arctic to the convection sites modulates the overturning circulation. The variability is sustained by an interplay between the storage and release of freshwater from the central Arctic and circulation changes in the Nordic Seas that are caused by variations in the Atlantic heat and salt transport. The relatively high resolution in the deep-water formation region and the Arctic Ocean suggests that a better representation of convective and frontal processes not only leads to an improvement in the mean state but also introduces new mechanisms determining multidecadal variability in large-scale ocean circulation.